On co-opetition between mobile network operators: Why and how competitors cooperate - Jan Markendahl; Bengt G. Mölleryd (International Telecommunications Society (ITS), 2012)
This paper address issues about cooperation among and competition between mobile network operators. The starting point is to examine why and how operators share infrastructure for mobile communication services, so called network sharing. The paper analyzes drivers, benefits and obstacles of network cooperation. We also analyze how roles and responsibilities are distributed for the network related functions while concurrently operators compete for customers and have separate functionality for service provisioning, marketing, customer relation management, charging and billing. Next, we analyze how network sharing as such and strategies for network sharing have changed in Sweden from the year 2000 when the 3G licenses were awarded and up to the year 2010. Moreover, network sharing in Sweden is compared with India where the market situation is different, as the number of operators is four times more and the cooperation is organized in another way, with separate tower companies, which provides base stations sites where operators are tenants. Finally, we compare the network sharing cases with how mobile operators organize cooperation for mobile payments services. From our empirical data we can identify four different types of co-opetition among mobile operators. 1. A co-operative spirit with focus on working practices and/or principles that will facilitate the common use of resources or solutions. 2. Infrastructure cooperation through a third party, e.g. a tower company or a SMS aggregator with the main objective to reduce costs or to provide a common solution. The operators have agreements with a third party but not with each other. 3. Infrastructure cooperation through a joint venture that is responsible for network deployment and operation. The driver is to achieve cost-savings. The operators have their own service provisioning, billing, customer relations management and compete for end-users. 4. Service and infrastructure cooperation through a joint venture that is fully responsible for providing the end-user service, in our case mobile payments. The main driver is to offer a payment solution common for all operators in order to complement or compete with solutions provided by banks or payment service providers.
Keywords: 330